PreVist project: prevention of victimisation in sex work in the canton of Vaud (Switzerland). Reflections from the criminological praxis - Molnar, Lorena (International e-journal of criminal sciences, 2019)
PreVist is a project created and implemented by the association Fleur de Pavé, a non-governmental organisation engaged in sex work risk minimisation in the canton of Vaud (Switzerland). Based on situational crime prevention strategies and existing research on the victimisation and stigmatisation of sex workers, this project aims to reduce the victimisation of sex workers. Three types of workshops were developed for the sex workers: "crime prevention and victims' rights," "what makes a good client" and "the need to be supportive and united". We conducted workshops with indoor and outdoor sex workers and their clients. As an additional measure, pocket alarms were distributed. To motivate prosocial behaviour, we developed a guide for clients which was handed out in the street prostitution area in Lausanne and in the erotic massage salons in the canton of Vaud. Although the project was perceived as useful by the target population, at this stage, its limitations are: a) the lack of systematic and rigorous experimental evaluation of the efficacity of the project, b) the limited room for manoeuvre of an association, and c) the risk of encouraging undocumented migrants to report crimes. To overcome these limitations, we suggest collaboration between academia and NGOs for the design, implementation and evaluation of such programs. Nonetheless, we hope that this project inspires other organisations to carry out prevention projects in this field.